Identity, emotion, and feminist collective action - Hercus, Cheryl (Gender and Society, 1999)
This article explores the relationship between identity, emotion, and feminist collective action. Based on interview research, the analysis confirms the central importance of anger in collective action and its particular significance for feminist identity and activism. As an emotion thought deviant for women, the anger inherent in feminist collective action frames created problems for participants in terms of relationships with partners, friends, and work colleagues. Participants performed emotion work to deal with negative responses to their feminist identity, but this depleted emotional energy and created stress. Participation in movement events provided much-needed emotional support and an outlet for deviant emotions.
Keywords: 1900-1999; 1990-1999; australie; colère; discipline; militance; océanie; organisations féministes; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; étude qualitative

The social construction of heterosexuality - Wilkinson, Sue; Kitzinger, Celia (Journal of Gender Studies, 1994)
Looks at some of the key issues raised by a tradition of social constructionist work on homosexuality, focusing on the nature of heterosexuality, heterosexual self-identification and the relationship between heterosexual sexual behavior and sexual identity. Political and theorectical importance of a sustained analysis of the functions and utility of heterosexuality; Impact of social constructionist theory on research relating to lesbians and gay men.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; premier cycle; psychologie; périodes historiques; sciences humaines; soc2014; sociologie; thématiques

J'aime à toi : esquisse d'une félicité dans l'histoire - Irigaray, Luce (Grasset, 1992)
Qui es-tu, toi qui n'es, ne seras jamais moi ni mien ? Je t'écoute comme la révélation d'une vérité irréductible à moi. Tu m'as saluée, reconnue. Tu interroges tes limites. Je te donne du silence où le futur de toi - et peut-être de moi avec toi - peut émerger et se fonder. Je ne m'approche pas immédiatement de toi. Je ne te connaîtrai jamais de manière absolue. Je laisse de l'air, de l'espace, du mystère autour de nous. Éveillée à toi, recueillie, j'invente des paroles qui te touchent de leur souffle sans t'enlever à toi. Cet abord intransitif cherche aide auprès de l'univers, de la beauté, de la sagesse, de l'Histoire. En cette uvre déjà, j'aime à toi. Puisse ce " à " garder l'intention entre nous encore et toujours vive, berceau de l'être que notre transcendance l'un à l'autre enfante. " Après une critique de la maîtrise de notre culture par le genre masculin et la définition de médiations nécessaires à la constitution du sujet féminin, Luce Irigaray élabore ici une dialectique de l'intersubjectivité fondée sur la différence sexuelle. J'aime à toi marque donc un nouveau temps dans l'ouvre de la philosophe, le premier ayant été ouvert par Speculum, De l'autre femme.
Keywords: 1900-1999; 1980-1989; cours; différence des sexes; discipline; europe; fem1000; france; philosophie; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; sujet féminin; thématiques; écriture des femmes*

La nature humaine est deux - Irigaray, Luce (J'aime à toi : esquisse d'une félicité dans l'histoire, 1992)
Keywords: 1900-1999; 1980-1989; cours; différence des sexes; discipline; europe; fem1000; france; philosophie; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; sujet féminin; thématiques; écriture des femmes*